Nove zamisli na 27. svetovnem kongresu "športa za vse" v Portorožu - Berčič, Herman (Šport (Ljubljana), 2022)
At the beginning of summer 2022, in the changed world circumstances, the 27th “Sport for All” world congress was held in Portorož. Its content was prepared by TAFISA, the leading Sport for All international and at the same time umbrella organisation. The organisation and implementation of the congress were entrusted to the Olympic Committee of Slovenia–Association of Sports Federations (OKS-ZŠZ) and the Sports Union of Slovenia (ŠUS). The patron of the congress was Borut Pahor, President of the Republic of Slovenia, who held a reception for the organisers in his presidential palace, thus giving this international event in Slovenia a special meaning. As the organisers wrote, the congress took place “at the heart of Europe”, under the meaningful motto “Sport for all in the changing world”. This global meeting of various experts, officials and managers from several continents and 382 organisations from 166 countries resulted in new findings and perspectives, including in the sphere of “sport for all”. These arise from the current times and the unpredictability of individual international events. However, the congress came to the indisputable conclusion that “sport for all” can be an important ingredient of people’s quality of life and healthy lifestyle in different parts of the world. The adopted resolution laid the ground for future development.
Keywords: družbene spremembe; kongresi; ocene in poročila; razvoj; resolucija; šport; šport za vse